2021
DOI: 10.3390/foods10061225
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Associated with Orange Fruit Color Increases Concentrations of β-Carotene in a Sweet Pepper Variety (Capsicum annuum L.)

Abstract: Pepper is the second most important vegetable crop in Bulgarian agriculture and has become the subject of extensive breeding programs that frequently employ induced mutagenesis. The success of breeding programs can be enhanced by the efficient and integral application of different biochemical and molecular methods to characterize specific mutant alleles. On the other hand, identifying new cost-effective methods is important under a limited-resources environment. In this paper we compare the levels of five heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…There is a competition among the three pathways for production of these secondary metabolites in G. uralensis. Several lines of evidence have demonstrated that overexpression of CRTZ increases the utilization of β-carotene (Pollmann et al 2017), while knockout of CRTZ has an opposite effect (Tomlekova et al 2021). It is thus expected that an accumulation of β-carotene by the CRTZ knockout leads to a feedback inhibition of the MEP pathway, which in turn promotes the MVA pathway and the production of GA in G. uralensis.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…There is a competition among the three pathways for production of these secondary metabolites in G. uralensis. Several lines of evidence have demonstrated that overexpression of CRTZ increases the utilization of β-carotene (Pollmann et al 2017), while knockout of CRTZ has an opposite effect (Tomlekova et al 2021). It is thus expected that an accumulation of β-carotene by the CRTZ knockout leads to a feedback inhibition of the MEP pathway, which in turn promotes the MVA pathway and the production of GA in G. uralensis.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…Zeaxanthin epoxidase ( ZEP ) mutants and silenced plants had higher total carotenoids and zeaxanthin and displayed orange-colored fruits in maturity . A candidate pseudo response regulator2 ( PRR2 ) was identified for the C1 locus that was crucial for carotenoid biosynthesis alongside functional PSY1 ( Y locus ) and CCS ( C2 locus ) in C. frutescens , C. chinense “Habanero”, and C. annuum “IT158782”. , Deletion mutations in α and β-carotene hydroxylase ( CrtZ chr3 and CrtZ chr6 ) genes led to higher α and β-carotene levels and are associated with orange color in mature fruits of pepper variety Oranzheva kapia . The PSY2 gene was found to complement PSY1 deletion mutation in C. annuum “MicroPep Yellow” in the basal carotenoid biosynthesis pathway .…”
Section: Biosynthesis and Transcriptional Regulation Of Capsicum Seco...mentioning
confidence: 99%
“…57,58 Deletion mutations in α and β-carotene hydroxylase (CrtZ chr3 and CrtZ chr6 ) genes led to higher α and β-carotene levels and are associated with orange color in mature fruits of pepper variety Oranzheva kapia. 59 The PSY2 gene was found to complement PSY1 deletion mutation in C. annuum "MicroPep Yellow" in the basal carotenoid biosynthesis pathway. 35 A total of 38 homologous structural genes of the carotenoid biosynthetic pathway and 17 regulatory TFs were identified in C. annuum during transcriptome analysis.…”
Section: Capsaicinoidsmentioning
confidence: 99%
“…Two genes, CaLCYB1 and CaLCYB2, have been discovered in the pepper genome, and their expression found to be associated with the presence of carotenoids [11]. The study of five cultivars, including the mutant Oranzheva kapia, showed that two hydroxylase genes, encoding CrtZchr03 and CrtZchr06, are present in pepper on chromosomes 3 and 6, and that deletion of the CrtZchr03 gene resulted in an increase in β-carotene accumulation [12]. Cotransformation of the genes responsible for β-carotene, 4,4 -ketolase (CrtW) and β-carotene 3,3 -hydroxylase (CrtZ), has been utilized to engineer transgenic organisms capable of producing astaxanthin, a naturally occurring carotenoid pigment known for its antioxidant properties and vibrant red-orange coloration [13].…”
Section: Introductionmentioning
confidence: 99%